Recobrimento radicular em classes I e II de Miller, associado a enxerto de conjuntivo subepitelial: ensaio clínico comparativo de duas técnicas. - Spada, Vitor Juliano (2015)
The aim of this study was to compare the effectiveness of two surgical root coverage techniques (semilunar coronally positioned flap and coronally advanced flap techniques) by using periodontal clinical parameters of periodontal tissues of patients with Miller Class I gingival recession. Twenty patients with ages between 20 and 50 years were selected. After basic periodontal treatment, the following were determined: plaque index, gingival index, probing depth, clinical attachment level and height of attached gingiva. Each patient was included into one of the following groups: Group 1: Semilunar coronally positioned flap technique; Group 2: coronally advanced flap technique. Patients were assessed for 180 days. The results showed significant reduction of plaque and gingival indexes in both groups as well as an improvement in the clinical attachment levels and probing depth. After 180 days, both techniques were effective for the health of periodontal tissues of patients with Miller Class I gingival recession and the most effective procedure was the coronally advanced flap technique due to significant gain in the clinical attachment level